Pendampingan Pembentukan PKBM (Pusat Kegiatan Belajar Masyarakat) di Desa Mandiangin Kecamatan Rawas Ilir Kabupaten Musi Rawas Utara - Sari, Inda Puspita; Nugroho, Agung; Sari, Septa Mila; Maryani, Kiki; Fitri, Enggi Wahyuni (Jurnal Pengabdi, 2020)
The aim of community service is to assist in the formation of the PKBM (Community Learning Center) in the Mandi Angin Village, Rawas Ilir, Musi Rawas Utara. The method used is the method of socialization, training and practice. This PKBM is a mentoring activity that drects to the formation of the PKBM structure (The center of community learning activities). This is the concern of the PKBM team because in the Mandi Angin village has not yet formed a learning center for the community. PKBM assistance activities (the center of community learning activities) will increase SDM leading to SDM productivity in Mandi Angin village. The results of the PKBM (community learning activity center) activities in the Mandi Angin village of Rawas Ilir sub-district, kabupaten Musi Rawas Utara, including: 1) The implementation of STKIP-PGRI Lubuklinggau team with the village government, so that the activities took place safely and smoothly, 2) The implementation of the socialization of the PKBM structure (community learning activity center) and responded wel by the community, 3) the device and the community who were enthusiastic in bathing to support the formation of PKBM in the village, 4) The constrains faced were related to the difficulty in getting high competent communities, as part of the PKBM structure, and 5) The village government and the community demanded that the PKBM activities be carried out well, not just in the form of structuring their activities. In general the results of this PKBM are the formation of the PKBM structure which will be continued at the level of PKBM implementation.